ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE CAMEL DI PT PANIN DUBAI SYARIAH BANK PERIODE 2016-2020 - Taufiq Ridwan Murtadho; Rizky Ridwansyah (UIN Sunan Gunung Djati Bandung, 2021)
Along with the era, sharia banking is now soaring. With a system that implements revenue sharing and free from maisyir elements. So the community began to switch to keep the money and conduct other transactions at sharia banks. Because of the increasing number of Sharia banks, every bank is required to be able to maintain the level of health of the bank. Because this becomes the foundation of whether the bank is able or not to manage funds from customers and this becomes the main foundation of stakeholder trust. In the process of assessing the health of the bank there are several provisions that have been set in writing by Bank Indonesia, so that anyone can easily analyze, one of them by using camel method. Because the assessment of the bank's health level becomes a benchmark to evaluate the management of the bank. The purpose of this study is to analyze the level of health of banks using camel method in PT. Bank Panin Dubai Syariah period 2016-2019, the overall results of the evaluation in general performance and health in fairly healthy condition.Keywords: Health, Bank, CAMEL